Understanding the molecular mosaic of cardiotoxicity of light chains in plasma cell dyscrasias and cardiac light chain amyloidosis with the use of patient derived full-length light chains. (3rd October 2022) - Nikolaou, P E; Georgoulis, A; Liacos, C; Makridakis, M; Efentakis, P; Baltatzis, G; Mavroidi, B; Pelecanou, M; Vlachou, A; Terpos, E; Vorgias, C E; Dimopoulos, M A; et al.
Abstract: Background: Cardiac light chain amyloidosis (AL-CA) is a life-threatening disease and the major determinant of prognosis in AL amyloidosis. The management of heart failure (HF) in AL is challenging and gold standard therapies for HF are poorly tolerated or ineffective. Cardiac toxicity of LCs in AL-CA is poorly understood and the comparison of cardiotoxicity of LCs derived from plasma cell dyscrasias (PCDs) such as multiple myeloma (MM) and monoclonal gammopathy of undetermined significance (MGUS), will improve our understanding of the mechanisms of cardiac damage. Purpose: We aimed to 1) genetically identify and biotechnologically produce full-length LCs from patients with AL-CA, MM, MGUS or non-clonal LCs from healthy volunteers (HV), 2) identify LCs' cardiotoxicity and 3) investigate the underlying mechanisms of cardiotoxicity in vitro. Methods: Bone marrow derived CD138+ cells from n=7 patients with AL-CA, n=2 patients with MM and n=2 patients with MGUS and peripheral blood mononuclear cells (PBMCs) from n=2 HV were isolated for RNA extraction and characterization of the LC gene family repertoire. At the protein level, LC expression was confirmed by immunoprecipitation in patients' serum followed by top-down proteomics. The overexpressed LC genes in each patient, encoding the full-length clonal LCs were cloned and produced in Shuffle E. coli cells. Two LCs were produced from HV based on the primary protein structure similarity with the patients' LCs. Primary adult ventricular murine cardiomyocytes (pAVMCs) were isolated and exposed at various LC concentrations for evaluation of cell death and investigation of the cardiotoxicity mechanisms via gene and protein expression. LCs folding, oligomerization and amyloidogenic potential were assessed via circular dichroism (CD), SDS page and electron microscopy respectively. Results: We successfully identified the LCs responsible for the disease and isolated the respective proteins in all cases (7 AL-CA, 2 MM, 2 MGUS and 3 HV). Despite the similarity of the LCs in conformation as beta-sheet and oligomerization mainly as dimers, 5 out of 7 AL-CA derived LCs led to a different extent of cardiotoxicity in pAVMCs compared to the HV, MM and MGUS derived LCs which did not alter cell viability. Interestingly, these 5 LCs bared the highest amyloidogenic potency. LCs induced different molecular responses leading to cardiomyocyte death. AL-CA proteins κ-type induced apoptosis and overexpression of endoplasmic reticulum stress (ERS) markers while LCs λ-type increased unfolded protein response (UPR) markers and autophagy without inducing apoptosis. All LCs of κ-type including from MM and MGUS patients led to inteleukin-6 mediated inflammation indicating that this mechanism is independent of the observed toxicity. Conclusions: AL-CA derived LCs induce cardiotoxicity, which correlates to their amyloidogenic potential via ERS, UPR, autophagy and apoptosis which can be considered targets for cardioprotection. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Hellenic Foundation for Research and Innovation